Between the Devil and the Deep Blue Sea: The Role of the Amundsen Sea Continental Shelf in Exchanges Between Ocean and Ice Shelves - Heywood, Karen; Biddle, Louise; Boehme, Lars; Dutrieux, Pierre; Fedak, Michael; Jenkins, Adrian; Jones, Richard; Kaiser, Jan; Mallett, Helen; Naveira Garabato, Alberto; Renfrew, Ian; Stevens, David; et al. (Oceanography, 2016)
The Amundsen Sea is a key region of Antarctica where ocean, atmosphere, sea ice, and ice sheet interact. For much of Antarctica, the relatively warm water of the open Southern Ocean (a few degrees above freezing) does not reach the Antarctic continental shelf in large volumes under current climate conditions. However, in the Amundsen Sea, warm water penetrates onto the continental shelf and provides heat that can melt the underside of the area’s floating ice shelves, thinning them. Here, we discuss how the ocean’s role in melting has come under increased scrutiny, present 2014 observations from the Amundsen Sea, and discuss their implications, highlighting aspects where understanding is still incomplete.